A novel low-loss wafer-level packaging of the RF-MEMS devices - PARK, YUN KWON; PARK HEUNG WOO; DUCK JUNG LEE; Park, J.-H.; Song, I.-S.; Kim, C.-W.; Song, C.-M.; LEE, YUN HI; Kim, C.-J.; Ju, B.-K. (Proceedings of the IEEE Micro Electro Mechanical Systems (MEMS), 2002)
In this work, the flip-chip method was used for packaging of the RF-MEMS switch on the quartz substrate with low losses. The 4-inch Pyrex glass was used as a package substrate and it was punched with airblast with 250 μm diameter holes. The Cr/Au seed layer was deposited on it and the vias were filled with plating gold. After forming the molds on the holes with thick photoresist, the bumps were plated on holes. The package substrate was bonded with the quartz substrate with the B-stage epoxy. The loss of the overall package structure was tested with a network analyzer and was within - 0.05 dB. This structure can be used for wafer level packaging of not only the RF-MEMS devices but also the MEMS devices.